1996
DOI: 10.1007/bf02104835
|View full text |Cite
|
Sign up to set email alerts
|

Ricci collineations of the Bianchi type II, VIII, and IX space-times

Abstract: Ricci and contracted Ricci collineations of the Bianchi type II, VIII, and IX space-times, associated with the vector fields of the form (i) one component of ξ a (x b ) is different from zero and (ii) two components of ξ a (x b ) are different from zero, for a, b = 1, 2, 3, 4, are presented. In subcase (i.b), which is ξ a = (0, ξ 2 (x a ), 0, 0), some known solutions are found, and in subcase (i.d), which is ξ a = (0, 0, 0, ξ 4 (x a )), choosing S(t) = const.×R(t), the Bianchi type II, VIII, and IX spacetimes … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0
3

Year Published

2001
2001
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 13 publications
1
19
0
3
Order By: Relevance
“…In this case, from eqs. (8), (9), (14), and (17), it follows that ξ 1 = ξ 1 (θ, φ), ξ 2 = ξ 2 (r, θ), and ξ 3 = ξ 3 (r, θ, φ). Then, from eq.…”
Section: Ricci Collineationsmentioning
confidence: 95%
See 2 more Smart Citations
“…In this case, from eqs. (8), (9), (14), and (17), it follows that ξ 1 = ξ 1 (θ, φ), ξ 2 = ξ 2 (r, θ), and ξ 3 = ξ 3 (r, θ, φ). Then, from eq.…”
Section: Ricci Collineationsmentioning
confidence: 95%
“…(13) and (17), ξ 3 = ξ 3 (θ, φ). When R 22 = 0, after a systematic integration of the equations (10) and (14) it is shown that RCV field is…”
Section: Ricci Collineationsmentioning
confidence: 99%
See 1 more Smart Citation
“…We consider a spatially homogeneous and anisotropic (LRS) Bianchi type-II metric is in the form [44][45][46][47] …”
Section: Metric and Field Equationsmentioning
confidence: 99%
“…An entire and significant work on CCs was published by Hall [4] in his book "Symmetries and Curvature Structure in General Relativity", where a classical discussion about other symmetries is also given. As the Ricci tensor is the trace of the Riemann tensor, the RCs have a natural geometric significance [7][8][9]. The physical importance of RCs is also investigated in the literature.…”
Section: Introductionmentioning
confidence: 99%